WHAT DRIVES EXPERIENTIAL LOYALTY TOWARDS THE ISLAMIC BANKS ? EVIDENCE FROM INDONESIA - Endang Hatma Juniwati; Agil Krisna Rivanda, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2023)
Purpose Indonesia has Muslim majority population, however the number of people who choose to be customer in sharia bank is still relatively small. The purpose of this study is to find out the influence of sharia finance literacy, profit-sharing ratio, income, and trust to the loyalty of customer of sharia bank. Design/methodology/approach The method used in this study is the explanatory research with quantitative approach. The data used in this study were based on criterion muslim and customer of sharia bank with participating respondents of 233 respondents from Bandung Raya. Findings The result of this study is that the variable of sharia finance literacy, profit-sharing ratio, and trust have significantly positive influence while variable of income do not have significant influence in the loyalty of customer to sharia bank. Practical implications The results will assist Islamic bank management in continuing to introduce Islamic banks to the public and try to get closer to them. The relevant sharia authorities should continue to introduce financial knowledge to the public, and if necessary make regulations that can accelerate these efforts.